(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Cloud technology acceptability and development are being endangered by unresolved cybersecurity issues that impact both the cloud operator and the cloud consumer. In this article, researchers show how virtualized may help secure public cloud by ensuring the integrity of the both guest virtual machines and cloud network equipment.. In specifically, we present the Advanced-Cloud-Protection-System (ACPS), a new construction targeted at ensuring improved security for cloud resources. ACPS may be used on a variety of cloud systems to efficiently while being anonymous to virtualization and cloud users, verify the validity of guest and network resources. Security breaches may be responded to nearby by ACPS, as well as notified to a higher security-management-layer. Two existing open source systems, Eucalyptus and Open ECP, have completely implemented a prototype of our ACPS concept. The prototype is put to the test in terms of efficiency and performance. In specifically, (a) the efficacy of our prototype is shown by testing it against known assaults in the nonfiction; (b) the ACPS prototype’s performance is evaluated under various kinds of workload. The results indicate that our approach is resistant to assaults and that the upstairs imposed is minimal when associated to the landscapes available.